1998
DOI: 10.1002/(sici)1521-4141(199803)28:03<914::aid-immu914>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of human T cell cytokine patterns and IgE and IgG4 responses by conformational antigen variants

Abstract: Bee venom phospholipase A2 (PLA) represents the major allergen and antigen in allergic and non-allergic individuals sensitized to bee sting. We have studied specific activation of peripheral T cells by different structural and conformational variants of PLA and secretion of cytokines regulating IgE and IgG4 antibody (Ab) formation. PLA molecules expressing the correctly folded tertiary structure, which show high affinity to membrane phospholipids and were recognized by Ab from bee sting allergic patients, indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 53 publications
5
45
0
2
Order By: Relevance
“…The strong lymphoproliferative responses induced by the rBet v 1 fragments can be explained by the fact that both fragments together resemble the T cell epitope repertoire of complete rBet v 1 and the fact that they were engineered by selecting the breakpoint between the fragments outside known Bet v 1-specific T cell epitopes (26,44). Our finding that rBet v 1 fragments were potent inducers of T cell responses are in line with a previous study demonstrating that changes in antigenic conformation to a non-IgE binding structure increases the T cell stimulation capacity and induces higher proliferation and IFN-␥ production leading to decreased IL-4/IFN-␥ and IgE/IgG ratios (45).…”
Section: Discussionsupporting
confidence: 88%
“…The strong lymphoproliferative responses induced by the rBet v 1 fragments can be explained by the fact that both fragments together resemble the T cell epitope repertoire of complete rBet v 1 and the fact that they were engineered by selecting the breakpoint between the fragments outside known Bet v 1-specific T cell epitopes (26,44). Our finding that rBet v 1 fragments were potent inducers of T cell responses are in line with a previous study demonstrating that changes in antigenic conformation to a non-IgE binding structure increases the T cell stimulation capacity and induces higher proliferation and IFN-␥ production leading to decreased IL-4/IFN-␥ and IgE/IgG ratios (45).…”
Section: Discussionsupporting
confidence: 88%
“…Investigators have shown that presentation of particular antigen-specific T-cell determinants can be enhanced or suppressed as a direct consequence of antibody modulation of antigen processing (6,48,67,78), and changes in the specificity of T-cell epitopes modulate the fine specificity of an antibody response (42,49). In addition, Milch et al (52) and Akdis et al (1) have reported that conformational variants of antigens can result in differences in cytokine expression by helper T cells, a factor in determination of murine Ig isotype (1,72,79). We speculate that changes in the susceptibility of P1 to proteolysis as a result of binding of anti-P1 MAbs would result in a different spectrum of peptides that interact with the antigen-specific T-cell repertoire and influence the spectrum of antibodies elicited during a polyclonal response.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was reported that the denatured form of recombinant bee venom PlA 2 allergen, which failed to bind to the specific Ab, tended to favor the induction of Th 1 cells in vitro, and that the effect was attributed to the absence of B cell-mediated Ag presentation (29). Because B cells specific for the Ags are expected to have much higher affinity for the Ag than other APCs, the preferential generation of Th2 cells with limited concentrations of Derf-2 may be ascribed partly to the difference in the APC.…”
Section: Discussionmentioning
confidence: 99%